Experience and perspectives on palliative or end-of-life care of Chinese people and their families as immigrants to high-income countries: a systematic review and thematic synthesis. Issue 12 (17th December 2020) - Kwok, Harley H Y; Low, Joesph; Devakumar, Delan; Candy, Bridget
Abstract : Background: A sizeable cohort of Chinese migrants in high-income non-Asian countries is reaching old age and many will develop life-limiting illnesses. They may benefit from palliative care, which is integrated into universal health coverage in many of these countries, but the uptake of this care among migrant communities remains low. Cultural differences between the Chinese and the host community, and poor language skills may be barriers to access, yet understanding the reasons hindering uptake are obscure. Aims: To understand the cultural perspective of how first generation Chinese migrants and their families perceive the provision of palliative care, to identify what exists which may limit their access in high-income non-Asian countries. Design: A systematic review and three-stage thematic synthesis of qualitative studies. Citations and full texts were reviewed against predefined inclusion criteria. All included studies were appraised for quality. Data source: MEDLINE, EMBASE, PsycINFO, CINAHL and PubMed were searched to July 2019. Results: Seven qualitative studies were identified (from USA, UK, Canada and Australia). Across the studies analytical themes that impacted on the use of palliative care services were identified: (1) migrants' intrinsic perceptions of cultural practices, (2) their expectations of and preparation for care at the end of life, (3) perspectives and influences of family and (4) knowledge and communication with palliative care providers in the host country. Key elements found that challenge access to palliative care services in the host countries were: Chinese culture is rooted in the core values of the family as opposed to the individual; migrants' limited experience in their place of origin in accessing healthcare; and practical issues including a lack of language skills of their host country. Conclusions: Palliative care services do not always match the needs of Chinese migrants in non-Asian high-income countries. Engagement and education on multiethnic cultural awareness in both the host non-migrant and the migrant communities is needed.